Birth, colostrum, and vigour traits of lambs born from Corriedale ewes grazing native pastures supplemented during the peripartum period - Olivera-Muzante, Julio; Fierro, Sergio; Durán, Juan Manuel; Antognazza, José; Sánchez, Santiago; Dutra, Fernando; Baldi, Fernando [UNESP]; Banchero, Georgget (Elsevier, 2022)
To evaluate the effect of a short-term energy-protein supplementation during the peripartum on birth, colostrum, and vigour traits of lambs, 214 multiparous Corriedale pregnant ewes grazing native pastures were used. Ewes, according to body conditions score and body weight, were assigned to a 2 × 2 factorial design: type of birth (single or twin), and supplementation (yes or no). Single (n = 67) and twin bearing (n = 39) non-supplemented, and single (n = 67) and twin bearing supplemented ewes (n = 41) were observed during lambing in two similar sub-paddocks. There was no detected interaction between supplementation and type of birth for any of the experimental variables (P > 0.05), except in the time the lambs took to stand after birth. Length of gestation and type of parturition (normal vs. dystocia) were not affected by supplementation or type of birth (P > 0.05). The duration of parturition (phase II) was longer in supplemented than non-supplemented and in single than in twin bearing ewes (P < 0.05). Colostrum production was greater, heavier, and less viscous in supplemented than non-supplemented ewes, and in single than twin bearing ewes (P < 0.05). Colostrum nutritional values were greater in supplemented than non-supplemented ewes; there was more total lactose in single than twin bearing ewes (P < 0.05). Birth weight of lambs was not affected by supplementation (P > 0.05), but it was higher in single than twin lambs (P < 0.05). There were more lambs with blood glucose concentration greater than 20 mg/dl at birth from supplemented than non-supplemented, and from single than twin bearing ewes (P < 0.05). There was no effect of supplementation in the time taken by lambs to stand and suck their mothers (P > 0.05), however in non-supplemented ewes, single lambs stood and sucked faster than twin lambs (P < 0.05). No differences in lamb mortality to 72 h were observed due to supplementation or type of birth (P > 0.05) but lesions of dystocia/stillbirth/birth injury as cause of death was less frequent in supplemented than non-supplemented ewes (P < 0.05), without differences by type of birth (P > 0.05). In conclusion, a short-term energy-protein supplementation in ewes during peripartum period influenced positively the volume, viscosity and composition of colostrum and blood glucose of lambs at birth, reducing lesions of dystocia/stillbirth/birth injury as cause of death of lambs, but did not affect the length of gestation, duration, or type of parturition in ewes, birth weight, lamb vigour, or lamb mortality to 72 h.
Keywords: Colostrum; Corriedale; Lamb Survival; Parturition; Supplementation; Vigour